Pertimbangan Aspek Sosio-Yuridis Terhadap Penggunaan Pasal 54 Undang-Undang Nomor 35 Tahun 2009 Tentang Narkotika - Brensby Williams Manuhutu; John Dirk Pasalbessy; Julianus Edwin Latupeirissa (Faculty of Law, Universitas Pattimura, 2022)
Introduction: The law has a broad perspective in looking at a crime. Crime is not just something that violates legal norms, but also every form of violation of various types of norms, both religious norms, morals, customs to legal norms. Developments that are increasingly advanced, of course crime is also more developed in people's lives, so we often encounter delinquency in the form of narcotics abuse.Purposes of the Research: This writing aims to examine and analyze the socio-juridical reasons for someone suspected of using narcotics to be rehabilitated according to Article 54 of Law Number 35 of 2009 concerning Narcotics, to examine and analyze the effect of the rehabilitation process on subsequent legal proceedings. Methods of the Research: Normative research method with the type of research is qualitative analysis. The problem approach used is the statute approach, the conceptual approach and the case approach. The sources of legal materials used are Primary legal materials, Secondary legal materials, and Tertiary legal materials and are used as a technique for collecting legal materials, then processing and analyzing legal materials through methods of interpretation, harmonization, systematic and legal discovery.Results of the Research: The results showed that rehabilitation is also an effort to restore and make narcotic addicts live physically and spiritually healthy so that they can adjust and improve their skills, knowledge, and intelligence in the environment. The integrated assessment mechanism that was born from concerns about the handling of narcotics abusers is expected to be the main gate for development in the field of law against narcotics abusers in the future.